El Excentrico, 1978-12-20 - Garcia, Bert:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2024)
December 20, 1978 [20 de diciembre de 1978]. Ano 29, No 18. Cover contains an illustration of two deer in a moonlit forest. The headline reads, "Merry Christmas y Prospero Ano Nuevo" (transl: and Happy New Year).